The conservation of biodiverse continuous forests and patches may provide services that support oil palm yield: evidence from satellite crop monitoring - Oon, Aslinda; Ahmad, Azizah; Md Sah, Syarina; Abdul Maulud, Khairul Nizam; Yahya, Muhammad Syafiq; Lechner, Alex M.; Azhar, Badrul (Elsevier BV, 2023)
Protecting natural forests such as those identified as high conservation value (HCV) areas may facilitate crop production due to the benefit from ecosystem services provided by biodiversity spill-over from adjacent forests. To investigate the effect of protecting contiguous and isolated forests adjacent to oil palm plantations on crop health, we measured the distance between oil palm plots and the continuous forest and forest patch boundaries. We surveyed 715 oil palm sample plots comprising 613 plots in large-scale oil palm plantation and 102 plots in smallholdings that were at least 300 m apart and had a radius of 100 m. Satellite imagery and ancillary spatial data from 2016, 2018, 2019 and 2020 of Negeri Sembilan, Malaysia were used to determine elevation and vegetation indices (VIs). The VIs derived were the Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI), and Normalized Difference Moisture Index (NDMI). Both NDVI and EVI are used to measure the vegetation greenness. The NDMI is used to determine the water content of plants. The VIs are crucial for a variety of applications, including vegetation monitoring, drought research, and agricultural operations. We then used generalized linear models (GLMs) to examine the relationship between VIs and stand-and landscape-level variables. Each VI was used as a response variable, with elevation, distance from continuous forest or forest patches, and oil palm management system (i.e., smallholding and industrial plantation) as explanatory variables. Our results revealed that the chlorophyll sensitive NDVI decreased with increasing distance from continuous forest, but increased away from the forest patches. In contrast, the dense vegetation sensitive EVI increased away from continuous forest, but decreased when distance from forest patches increased. Proximity to continuous forests or forest patches had no effect on the NDMI. All the vegetation indices were lower in smallholdings than industrial plantations. None of the vegetation indices were significantly influenced by elevation. Given that these indices predict palm health and yield, this pattern could result in greater ecosystem services that benefit oil palm growers in oil palm closer to some forest types through the spillover effects of forest biodiversity from continuous forests and forest patches. This study suggests that conservation and industry stakeholders should work together to strengthen the conservation of biodiverse continuous forests and forest patches in HCV standard to develop more-sustainable oil palm agriculture, because of their potential role in supporting ecosystem services.